PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN KEPUASAN SEBAGAI VARIABEL INTERVENING TERHADAP LOYALITAS ANGGOTA (Studi Kasus Pada KSPP BMT NU Gapura Kec. Gapura Kab. Sumenep) - Zairozie Tamim; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThis research are based on interesting phenomenon about the existence of koperasi as one of economic institution, which holds a familial bonds, Transcend beyond its glory, and loyal to it's members. The purpose of this research is to find out and analyze whether there is influence of googled customer relationship management (CRM) as X variables, meanwhile Y1 as intervening variables due to customer satisfaction and Y2 as customer loyalty. The research results showed that there was a significant influence between copied customer relationship management towards the pasted customer satisfaction. Therefore Y1 as satisfaction variable influences Y2 as loyalty. Therefore customer loyalty significantly benefitted credits towards translator directly. As advised by KSPP BMT NU Gapura to keep improving the costumer relationship management so that we can achieve customer loyalty by giving their satisfaction. Keywords : KSPP BMT NU, Customer Relationship Management, Customer Satisfaction, Customer Loyalty.